Role of water infrastructure programs for family farmers in strengthening adaptive capacities to climate change: lessons from the Cisterns Program in Semi-arid Brazil - Mesquita, Patrícia dos Santos; Cavalcante, Louise (Sustainability in Debate, 2021)
The semi-arid region of Brazil, marked by low human development indicators, has historically suffered from water scarcity, being the focus of public policies to reduce socioeconomic, water, and climatic vulnerabilities for more than a century. Among the recent initiatives, the Cisterns Program stands out as an attempt to guarantee water and food security for family farmers through the construction of social technologies for water storage, such as cisterns production. Thus, the research objective was to analyse the perception of farmers and institutional actors involved with the Program about the impact of the 2011-2018 drought on the functioning of cisterns and to discuss how water infrastructure programs can improve the adaptive capacity of farmers affected by climate change. Through semi-structured interviews with institutional actors at the regional/national level and with farmers in semi-arid Brazil in the years of 2017/2018, the results indicate that access to the social technology seems to strengthen the relationship between water and food security, and the specific capacity of farmers in dealing with climatic risks. We conclude with lessons and recommendations from the Brazilian experience that can be useful for actors from other semi-arid regions involved in water infrastructure programs.